2009
DOI: 10.1074/jbc.m109.001537
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin and Nucleolin Regulate K-Ras Plasma Membrane Interactions and MAPK Signal Transduction

Abstract: The spatial organization of Ras proteins into nanoclusters on the inner leaflet of the plasma membrane is essential for high fidelity signaling through the MAPK pathway. Here we identify two selective regulators of K-Ras nanoclustering from a proteomic screen for K-Ras interacting proteins. Nucleophosmin (NPM) and nucleolin are predominantly localized to the nucleolus but also have extranuclear functions. We show that a subset of NPM and nucleolin localizes to the inner leaflet of plasma membrane and forms spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 42 publications
3
62
0
Order By: Relevance
“…Nucleolin was reported previously to interact with K-Ras4B but not with H-Ras in the nucleolus (32). In a study published during the final preparation of our manuscript, it was reported that nucleolin from postnuclear supernatants of BHK cells interacts with K-Ras but not with H-Ras (43). The basis for this discrepancy is currently unclear.…”
Section: Discussionmentioning
confidence: 49%
“…Nucleolin was reported previously to interact with K-Ras4B but not with H-Ras in the nucleolus (32). In a study published during the final preparation of our manuscript, it was reported that nucleolin from postnuclear supernatants of BHK cells interacts with K-Ras but not with H-Ras (43). The basis for this discrepancy is currently unclear.…”
Section: Discussionmentioning
confidence: 49%
“…This interaction may further be modulated through phosphorylation of Ras at the C terminus (31). Additionally, certain membrane proteins, such as galectin (32), nucleophosmin (33), and calmodulin (34) could serve as scaffolds to bring two or more Ras proteins into proximity. Lastly, albeit secondary in driving Ras dimer formation, direct G-domain contacts between the two Ras proteins should not be ruled out based on existing data.…”
Section: Discussionmentioning
confidence: 99%
“…59,60 Moreover, it has been reported the interaction of the nucleocytoplasmic shuttling proteins Nucleophosmin and Nucleolin with KRAS to enhance nanocluster formation and signal gain in the MAPK pathway. 15 Thus, the functional interaction of the cytoplasm confined KRAS with HNRNPA2B1 could be understood in the context of a novel hnRNP cytoplasmic function.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, emergence of new regulators either by direct interaction or by reversible post-translational modifications, proved to be crucial to fully display KRAS oncogenic phenotype. Interaction of KRAS with Galectin-3, 11 calmodulin, 12 and PDEÎŽ 13,14 or with the initially-defined nuclear protein Nucleophosmin and Nucleolin, 15 proved to be necessary for correct activation of RAF/MEK/ERK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%